2022
DOI: 10.7759/cureus.21446
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neutrophil-Lymphocyte-Ratio (NLR) and Platelet-Lymphocyte-Ratio (PLR) as a Biomarker for Distinguishing Between Complicated and Uncomplicated Appendicitis

Abstract: IntroductionAcute appendicitis (AA) is one of the most common acute general surgical presentations affecting 7% of the population at some point in their lifetime. The ability to assess the risk of complicated appendicitis (CA) from uncomplicated appendicitis (UA) in acute appendicitis (AA) could reduce the associated morbidity and mortality. The value of platelet lymphocyte ratio (PLR) as an inflammatory marker increases when its fluctuations are interpreted along with other complementary hematologic indices, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
5
0
2
Order By: Relevance
“…Moreover, it has been proposed to use inflammatory biomarkers such as white blood cell (WBC) count, C-reactive protein (CRP), bilirubin level, immature granulocyte ratio, neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR) to enable early diagnosis of AA and reduce the rate of misdiagnosis [ 4 , 5 ]. In addition, a study conducted on children revealed that MLR could be used to diagnose AA [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been proposed to use inflammatory biomarkers such as white blood cell (WBC) count, C-reactive protein (CRP), bilirubin level, immature granulocyte ratio, neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR) to enable early diagnosis of AA and reduce the rate of misdiagnosis [ 4 , 5 ]. In addition, a study conducted on children revealed that MLR could be used to diagnose AA [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Delgado y colaboradores 24 , tomaron un punto de corte de INL >8.75 para estimar apendicitis complicada con sensibilidad y especificidad de 75% y 72% respectivamente. Se encontraron puntos de corte de INL inferiores a la presente investigación como el de Rajalingam y colaboradores 25 , que fue de 6.96 para apendicitis complicada, y de 6.17 en el estudio de Ahmad 26 ; en este mismo sentido cabe mencionar los estudios de Khan y colaboradores 27 , que reportaron asociación significativa para apendicitis complicada con un INL >6.36 y el de Jung y colaboradores 28…”
Section: Discussionunclassified
“…Clinical scoring systems can predict complicated appendicitis to a certain degree. Similarly, biochemical markers can distinguish between uncomplicated and complicated appendicitis [ 63 , 73 , 74 ]. CT scan findings of complicated appendicitis include Extraluminal appendicolith, abscess, appendiceal wall enhancement defect, extraluminal air, ileus, peri appendiceal fluid collection, ascites, intraluminal air, and intraluminal appendicolith; however, their sensitivity is limited.…”
Section: Reviewmentioning
confidence: 99%